The spread of Brazilian science through the advancement of written proficiency in English: a matter that cannot be postponed - Freitas, Ana Luiza Pires de (Brazilian Journal of Sexually Transmitted Diseases, 2020)
A recent bulletin from the Universidade de São Paulo(1) states that 168,546 scientific publications on the topic of COVID-19 have been issued worldwide in 2020. Records from the Dimensions Database Platform refer a mere 4,029 or 2.3% of them as sourced from Brazil. We could wonder what makes the figures of national publications that scanty. Financial cuts for academic research, the possibly excessive bureaucracy concerning clinical trial implementation, and the lack of Brazilian representativeness could also be associated with pressing problems, such as a poor mastery of the English language among Brazilian scientists. Nevertheless, publishing in high-impact journals, and hence forwarding the national research to an elevated pattern, implies a suitable use of the lingua franca of science so as to cooperate and liaise with the international scientific community. [...]